Does the inclusion of the cost and burden of adverse drug reactions associated with drug-resistant TB treatment affect the incremental cost-effectiveness of new treatment regimens? A case study from the introduction of bedaquiline in South Africa National TB Programme - Bistline, Kathryn Lou (Department of Public Health and Family Medicine, 2018)
South Africa has one of the world’s highest burdens of TB, HIV/TB co-infection, and drug-resistant TB. Second-line TB treatment is less effective, more expensive, and more toxic than treatment for drug-sensitive TB. Nearly 1 in every 5 persons who starts treatment for drug-resistant TB in South Africa will die; 1 in every 3 persons who survives treatments experiences permanent, profound hearing loss. For decades there was little progress in TB research, however, and so treatment with old regimens continued despite safety concerns. In 2012 the US and European regulatory authorities approved a new drug, bedaquiline, but only for treatment in cases with no other options. In 2015, the South African Medicines Control Council approved bedaquiline for drug-resistant TB, but only a limited number of doses were approved in the 2016/2017 annual budget and the focus, again, was only for the patients who had no other options. In order to inform policy makers in planning and budgeting for drug-resistant TB treatment, the aim of this thesis was to determine whether the simple calculation that bedaquiline was too expensive relative to standard regimens using kanamycin was too simple. Particularly, given the high burden of adverse drug reactions (ADR) associated with kanamycin, would the inclusion of the cost and burden of ADR affect the incremental cost effectiveness ratio of a new treatment regimen where bedaquiline replaces kanamycin? Analysis of the national drug-resistant TB case register showed that mortality during second-line treatment was early, primarily in the first 6 months of treatment, even when patients do not have extensive drug resistance. HIV-positive patients not on anti-retroviral therapy (ART) at initiation of drug-resistant TB treatment have the highest risk of mortality. The high early mortality is a real risk that clinicians have to balance when deciding to initiate ART and effective second-line TB treatment both as quickly as possible. Daily injections coupled with taking more than 10 pills each day are a heavy burden for patient compliance, but also pose concerns in terms of overlapping and compounding toxicities; this burden was confirmed through a meta-analysis of the pooled frequency of adverse events among cohorts with at least 25% of the patients HIV-positive. A competing risk analysis of a cohort of drug-resistant TB patients from Johannesburg – addressing the reality that patients may not have experienced an ADR because they died rather than because they were at lower risk – indicated that HIV-infected patients who are not yet stable on ART and second-line TB treatment are at the highest risk of ADR. A Markov model built and parameterized using the data from the South African national TB programme indicates that bedaquiline for all drug-resistant TB led to a small gain in effectiveness at a cost that was under the costs of the drug itself, due to savings from daily injection visits. While cost-effective, it was not clear that South African policy makers needed to move beyond the offer of bedaquiline for patients with extensive drug resistance. However, the calculation, and the decision point, were different once the costs and disability associated with ADRs was included in the analysis. Bedaquiline-based regimens offer a cost-saving and more effective alternative to an injection-based regimen for drug-resistant TB patients treated in the public sector in South Africa.